Preliminary Analysis of Factors Affecting Communities in Management of Stool at Sources in the Jakarta Communal Wastewater Treatment Service Area - Muhammad Ridho Marsono; Betanti Ridhosari; I Wayan Koko Suryawan; Evi Siti Sofiyah; Ariyanti Sawono; Nurulbaiti Listyendah Zahra (International Journal of Built Environment and Scientific Research, 2023)
This study examines the public perception of several Jakarta communities served by communal WWTPs on in situ management or wastewater sources and the relationship between factors. This research used a questionnaire and random sampling technic. The questionnaire is based on study indicators. This study uses nine domestic wastewater indicators. The corrected Item-Total correlation indicates that the variable is invalid and does not need to be continued to the reliability test. The Kaiser-Meyer-Olkin (KMO) and Bartlett's Test showed that factor analysis is appropriate. This study groups indicators into four dimensions. Factor 1 includes septic tank draining, sewage treatment, subscribing to sewage treatment, feces sludge management, and sewage sludge disposal. Second, septic tank performance and draining. Third, open defecation and septic tank owner are factors 2 and 4. Fourth, delete indicators with the same variable but different dimensions.